A risk assessment of fur seals interactions with aquaculture in Tasmania - Mark Hindell; Mary-Anne Lea; Heidi Auman (2013)
Salmon aquaculture in Tasmania is a well established and growing part of the State’s primary industry. Farming Atlantic salmon involves holding very large numbers of fish in large pens suspended in the sea, typically in groups of 10 or more pens known as a farm. The farms are all coastal and located around Tasmania in areas that meet particular requirements of coastal and bathymetric topography and current flow. This high concentration of fish overlaps with the normal range of fur seals, and inevitably results in seals being attracted to pens in an attempt to access the fish. The first harvest of salmon from aquaculture in Tasmania occurred in 1987 (53 tonnes), so seals have been interacting with fish farms for more than 25 years. As the industry has grown (now 40,000 tonnes annually, (TSGA 2013)), the number of interactions has also increased.